Informe de coyuntura: Diciembre 1996 - Quiñónez Avila, R.; De Calderón, V.; Cruz Palencia, E.A. (San Salvador (El Salvador), 1996)
Sumario (Es)
Ilus.
Keywords: ECONOMIA AGRICOLA; SITUACION ECONOMICA; COMPORTAMIENTO ECONOMICO; POLITICA ECONOMICA; LEGISLACION; PRECIOS; CREDITO; PRODUCCION; SECTOR AGRARIO; CAFE; AZUCAR; GRANOS; COMERCIO INTERNACIONAL